2016
DOI: 10.1016/j.jhazmat.2016.05.090
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic inhibition of PCDD/F formation from pentachlorophenol by mixtures of urea and calcium oxide

Abstract: h i g h l i g h t s• Mixed CaO/urea have a synergetic inhibition effect for PCDD/Fs formation from PCP.• 5-20% urea reaction systems obtained the better synergetic inhibition effect.• 2,3,7,8-PCDD congeners were the dominant products in eight reaction systems.• Intermediates could promote the acid-base reaction to realize synergetic inhibition. a r t i c l e i n f o b s t r a c tChlorophenols are structurally similar to PCDD/Fs and have been considered as highly potential precursors for PCDD/Fs formation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It has been widely reported that Cl 2 plays an essential role in the generation of C–Cl bonds, which more effectively promote the chlorination reaction of PCDD/Fs than HCl . Previous studies have tried to determine the inhibition mechanism of sulfur-based inhibitors and reported that sulfur could convert Cl 2 to HCl . As the TG-MS spectra in Figure show, the decomposition products (primary SO 2 and NH 3 with a strong reduction capability) from the inhibitor could react with Cl 2 to generate HCl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that Cl 2 plays an essential role in the generation of C–Cl bonds, which more effectively promote the chlorination reaction of PCDD/Fs than HCl . Previous studies have tried to determine the inhibition mechanism of sulfur-based inhibitors and reported that sulfur could convert Cl 2 to HCl . As the TG-MS spectra in Figure show, the decomposition products (primary SO 2 and NH 3 with a strong reduction capability) from the inhibitor could react with Cl 2 to generate HCl.…”
Section: Resultsmentioning
confidence: 99%
“…44 Previous studies have tried to determine the inhibition mechanism of sulfur-based inhibitors and reported that sulfur could convert Cl 2 to HCl. 45 As the TG-MS spectra in Figure 5 show, the decomposition products (primary SO 2 and NH 3 with a strong reduction capability) from the inhibitor could react with Cl 2 to generate HCl. Consequently, the chlorination reaction was effectively suppressed and the organic chlorine content decreased after injection of the inhibitor.…”
Section: Effect Of the Inhibitor On The Variation Of Morphology And C...mentioning
confidence: 99%
“…Numerous studies have been conducted to investigate the suppression effects of alkaline compounds on PCDD/F formation. Liu et al found that CaO could inhibit more than 90% of PCDD/F formation from PCP. CaO could consume acidic compounds such as HCl and Cl 2 resulting from a low concentration of chlorine and weakening the chlorination of PCDD/Fs.…”
Section: Dioxin Prevention Remediation and Reductionmentioning
confidence: 99%
“…Chemical inhibition is a low-cost and highly efficient technique to reduce UP-POP formation and emissions at the source. , Many previous studies used N/S-based inhibitors, such as urea, NH 3 , amidosulfonic acid, and other S-containing substances. Inhibitory effects were observed both in the laboratory and in full-scale municipal solid waste incinerators, and the mechanism of action underlying the inhibitory effects of thiourea in combustion flue gas was also clarified. , Lone-pair electrons of N and S in N/S-containing inhibitors are able to form stable complexes with catalytic metals to retard the activity of the catalyst. , Our group previously utilized thiourea in the iron sintering process and achieved total CBz and PCB emission concentration reductions of 78.2 and 83.0%, respectively . The thermal properties and chemical structures of N/S-containing compounds may influence the decomposition of N/S-containing products .…”
Section: Introductionmentioning
confidence: 99%